TASAWUF EKOLOGI (Tasawuf Sebagai Solusi dalam Menanggulangi Krisis Lingkungan) - Amat Zuhri (IAIN Pekalongan, 2009)
Human beings’ greed in exploiting nature excessively happens because of two things. First, human beings focus on their function as leader more. Second, they lose their awareness that they should be responsible for their in the presence of God. This attitude surely will cause nature damage that it, finally, brings about ecological damage. Therefore, nature damage can be coped with Islamic spiritual values that are promoted by tasawuf. Some of them are zuhud, wara’, faqir, fana-baqa, wahdat al-wujud and insan kamil. By internalizing those teachings, someone will be able to control himself in utilizing nature and increase his awareness to maintain nature with love.